Continuous recording of coronary sinus oxygen saturation during atrial pacing in patients with coronary artery disease or with syndrome X. Issue 1 (January 1988) - Crake, T; Canepa-Anson, R; Shapiro, L; Poole-Wilson, P A
Abstract : Coronary sinus oxygen saturation was measured continuously during incremental atrial pacing in 34 patients undergoing cardiac catheterisation. In eleven patients with normal coronary arteriograms, negative exercise tests, and no ST segment depression on the electrocardiogram, an increase in the rate of atrial pacing transiently decreased coronary sinus oxygen saturation but within 20 s oxygen saturation returned to the control value. In six patients with coronary artery disease ST segment depression developed during atrial pacing. The coronary sinus oxygen saturation fell and remained reduced until pacing was discontinued. The size of the fall of coronary sinus oxygen saturation increased with increasing heart rate. In seven patients with coronary artery disease the ST segments were unaltered during atrial pacing and coronary sinus oxygen saturation did not fall. Ten patients with syndrome X were studied. In six ST segment depression developed on atrial pacing. In five, three of whom developed ST segment depression, the changes in coronary sinus oxygen saturation during atrial pacing were similar to those observed in patients without any evidence of coronary artery disease. In three, all of whom developed ST segment depression, coronary sinus oxygen saturation gradually increased throughout the period of atrial pacing. In two patients coronary sinus oxygen saturation fell in a manner similar to that observed in patients with obstructive coronary artery disease who developed ST segment depression on pacing. Thus regulation of coronary blood flow in normal persons in response to an increase of heart rate is rapid. Oxygen extraction across the coronary bed can increase by up to 30% and a persistent increase in oxygen extraction is an indicator of myocardial ischaemia. The term "syndrome X" does not describe a homogeneous group of patients but in the majority coronary sinus oxygen saturation does not fall despite symptoms and changes on the electrocardiogram, indicating that inadequate coronary blood flow is not the dominant mechanism.